Pecha Kucha: An Effective Strategy for Teaching Speaking in an Indonesian Junior High School - Muzahira, Rofiatun; Zuhriyah, Mukminatus (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2024)
The students’ uninterest in joining their speaking class caused their low speaking skills. They were not interested because the strategy used by the English teacher when teaching was not interesting. Therefore, the researchers used Pecha Kucha strategy to teach them speaking in this present study. The objectives of this study were to know: (1) the students’ speaking skills before being taught using Pecha Kucha, (2) the students’ speaking skills after being taught using Pecha Kucha and (3) whether or not there was any significant effectiveness of using Pecha Kucha for teaching speaking. This pre-experimental study used a one group pre-test post-test design. This study was conducted in one of state junior high schools located in Diwek, Jombang, Indonesia. The population of this research was class VIII of that school. They consisted of 256 students. Meanwhile, the sample was class VIII B comprising of 32 students. This sample was taken using a purposive sampling. The instruments used for collecting the data were the pre-test and post-test. After the data were collected, the researchers analysed the data using statistical descriptive and a paired-sample t-test. The results indicated that: (1) the students’ speaking skills before the implementation of Pecha Kucha was low, (2) the students’ speaking skills after the implementation of Pecha Kucha was excellent and (3) Pecha Kucha was effective for teaching speaking. It is highly recommended that the students and the English teachers use Pecha Kucha in their speaking classes.